Clinician-teachers’ Self-assessments Versus Learners’ Perceptions - Windish, Donna M (Blackwell Science Inc, 2004)
Understanding how clinician-teachers’ self-assessments compare to learners’ impressions can serve to help educators place each of these evaluations in the appropriate context. Past participants of the Johns Hopkins Faculty Development Program and other physician-teachers were surveyed in 2002 regarding their teaching skills and behaviors. We surveyed their learners to compare teacher and learner assessments of teaching proficiency, behaviors, enjoyment, and career satisfaction. In each area, learners’ ratings were statistically significantly higher than their teachers’ self-ratings. Though it is unclear whether teachers’ or learners’ assessments are a more accurate reflection of the truth, the more positive learner ratings should promote self-confidence in clinician-educators regarding their teaching abilities.